Research progress in precision medicine for type 2 diabetes based on the GLP-1 - Wang, Sangui; Yuan, Chenrong; Wang, Haifeng; Ye, Xiyin; Ruan, Shun; Yi, Li; Yang, Wanyong; Wang, Zhi; Wang, Ni; Li, Jiahao; Feng, Xiaohui; Li, Yun; et al. (Frontiers in Endocrinology, 2026)
Diabetes Mellitus (DM) represents a global health crisis, currently affecting approximately 9% of the world’s population. Its prevalence continues to rise steadily, with a noticeable trend toward onset at younger ages. Projections indicate that the prevalence will reach 12% by 2045 equivalent to 820 million cases—positioning DM as one of the most serious public health threats worldwide. Pathogenetically, DM is classified into Type 1 Diabetes Mellitus (T1DM) and Type 2 Diabetes Mellitus (T2DM), with T2DM accounting for over 90% of all cases. T2DM is characterized by pancreatic β-cell dysfunction and insulin resistance, and is recognized as a multisystem metabolic disorder involving pathways such as the gut-brain axis, insulin/peripheral resistance, etc strongly correlated with obesity and cardiovascular diseases. Recent advances in basic medical research and clinical therapeutics have optimized the application of glucagon-like peptide-1 (GLP-1), establishing it as a cornerstone incretin based therapy for T2DM management. In parallel, metabolic surgery has demonstrated significant potential in ameliorating symptoms of T2DM. This article comprehensively reviews current trends in T2DM treatment, the molecular profile of GLP-1, biological characteristics of GLP-1-secreting L-cells, the development of GLP-1-related pharmaceuticals, and advances in metabolic surgery (MS). We searched the primary literature in PubMed, Embase and SciELO from inception to June 2025, using the terms “diabetes”, “type 2 diabetes mellitus”, “glucagon-like peptide-1”, “L-cell”, “metabolic surgery”, “jejunostomy”, “GLP-1 receptor agonists” as well as their combinations. We included basic/mechanistic studies, human observational studies, randomized clinical trials and observational post hoc analyses of trials that were relevant to the review topic. The aim is to provide insights and references for future strategies in personalized precision medicine for T2DM.